Reengineering Proses Bisnis Toko Oleh-Oleh Menggunakan Enterprise Resource Planning Odoo 13 dengan User Acceptance Test sebagai Metode Pengujian Sistem - I Kadek Suabdinegara; Gusti Agung Ayu Putri; I Made Sunia Raharja (STMIK Budi Darma, 2021)
Business process engineering is carried out on the business process of Wardani’s souvenir shop which is located at Jl. Monkey Forest, Ubud. This shop was chosen as the research use case because the shop is located in a strategic tourist location in the center of Ubud. Reengineering is focused on the Wardani Store’s business activities in the purchasing, inventory, and sales business functions, where at the time the research was conducted, all processes were still using the manual method. This method often causes problems, such as uncontrolled purchasing of goods, errors in recording purchases and sales of goods, length of calculation in transactions, and unclear information on availability of goods. Therefore, an approach is needed in developing an integrated system in the company's operational activities, and the application of Enterprise Resource Planning (ERP) can be an alternative in overcoming the problems experienced. ERP implementation is carried out by identifying ongoing business processes for purchasing, inventory, and selling goods, then making an integrated system proposal by implementing Odoo 13. System testing is carried out using the User Acceptance Test (UAT) method which is a final testing method for developing a product to validate whether the system built is in accordance with the user's needs or not. The system test results show that the Odoo ERP application is considered quite successful in helping companies in purchasing, inventory, and selling goods, so that business processes become more effective and efficient